Cryptosporidiosis in chickens - Prando, Luciana [UNESP]; Teixeira, Weslen Fabricio Pires [UNESP]; Alves, Graziella Borges [UNESP]; Cruz, Breno Cayeiro [UNESP]; Lopes, Welber Daniel Zanetti; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2017)
Among parasitic infections in poultry, the most common is cripitosporidiose. The genus Cryptosporidium causes infections that can lead to significant economic losses in the poultry industry, both cutting and posture, it's the most important pathogenic species Cryptosporidium baileyi, C. meleagridis and C. galli. The third most common cause of human cripitosporidiose is caused by C. meleagridis, being of great importance to public health and C. baileyi to cause severe infection, usually subclinical in Bursa of Fabricius, which is responsible for the immune system of birds. Thus, the birds play an important role in outbreaks of cryptosporidiosis and mechanical carriers of Cryptosporidium because they sporadically have the ability to spread oocysts, which can contaminate the ground water and, playing an important role in outbreaks of cryptosporidiosis.
Keywords: Broilers chicken; Cryptosporidiosis; Vaccine; Zoonosis